2020
DOI: 10.1177/1753193420936543
|View full text |Cite
|
Sign up to set email alerts
|

Infection after buried or exposed K-wire fixation of distal radial fractures: a randomized clinical trial

Abstract: We treated 220 extra-articular distal radial fractures with closed reduction and percutaneous K-wire fixation and randomized K-wire placement to buried or exposed. We analysed the incidence and severity of infection and the mobility of the metacarpophalangeal joints. At 6 weeks postoperatively, 12 patients in the exposed group had infections versus two in the buried group, which was a statistically significant difference. Mobility was statistically but not clinically better in the buried group. One pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Techniques employed by surgeons lack robust evidence regarding their utility. There are only eight trials evaluating antimicrobial techniques in hand trauma surgery, [35][36][37][38][39][40][41][42] five of which evaluated the effect of systemic antibiotics in open hand trauma, and three evaluated SSI after Kirschner (K)-wire fixation of hand and wrist fractures. A meta-analysis of studies assessing the use of antibiotics in open hand trauma revealed no significant distinction between antibiotic use or not.…”
Section: Discussionmentioning
confidence: 99%
“…Techniques employed by surgeons lack robust evidence regarding their utility. There are only eight trials evaluating antimicrobial techniques in hand trauma surgery, [35][36][37][38][39][40][41][42] five of which evaluated the effect of systemic antibiotics in open hand trauma, and three evaluated SSI after Kirschner (K)-wire fixation of hand and wrist fractures. A meta-analysis of studies assessing the use of antibiotics in open hand trauma revealed no significant distinction between antibiotic use or not.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of bias assessment by using the RoB v2 tool revealed that only 1 RCT [9] had a "low risk" of bias in all five assessment domains. The remaining four RCTs [10,[17][18][19] were judged to have "some concern" risk of bias.…”
Section: Quality Of Study Assessmentmentioning
confidence: 99%
“…Several studies have been conducted to compare buried and exposed K-wires in the management of hand and forearm fractures but have yielded inconsistent results. [9,10] A randomized trial study conducted by Maradei-Pereira JAR et al[9] distal radial, fractures showed a greater risk of infection when K-wires were left exposed than when they were buried. On the other hand, Khaled M et al[10] showed no significant difference in the complication rate, including pin infection incidence between exposed and buried K-wire.…”
Section: Introductionmentioning
confidence: 99%
“…Kirschner wire fixation is often used for hand and wrist fractures. There is a good deal of evidence that superficial wires are associated with a high rate of infection and that burying the wires beneath the skin decreases the frequency of this complication [70][71][72] .…”
Section: Fracture Carementioning
confidence: 99%